Deteksi Keberadaan Bakteri Staphylococcus di Udara Dalam Ruangan Pasar Tradisional Kota Pontianak - Rikhsan Kurniatuhadi, M. Arief Faturrahman, Rahmawati (Jurnal Protobiont, 2019)
Bacteria belongs to the genus of Staphylococcus is pathogenic bacteria and its existence is an indicator of contaminated environment particularly in the air. The aim of this study is to detect the existence of bacteria belongs to Staphylococcus in the traditional market space of Pontianak city. The study was conducted in January - March 2018. Sampling was administered in 4 traditional markets of Pontianak City using volumetric air sampling along with a vacuum air pump YYP 550-12A1 with an air flow rate of 26 l / min for 6 minutes using Mannitol Salt Agar (MSA). The results showed that air bacteria member of the genus Staphylococcus found in all traditional markets in the city of Pontianak. The lowest number of bacteria belongs to the lowest Staphylococcus genus in the Flamboyan Market was 15 CFU/m3 and the highest was in Pasar Mawar 89 CFU/m3. The data indicates the air in the traditional market of Pontianak City has not fully fulfill the air health standards according to Sedyaningsih (2011), which is free of pathogenic bacteria 0 CFU/m3.